Developing metadata application profiles - Malta, Mariana Curado 1969- (Advances in web technologies and engineering (AWTE) book series, 2017)
"This book is concerned with the processes for development of metadata application profiles, in an increasingly complex world of data, information standards and requirements for data exchange and interoperability. The chapters in this book cover a range of approaches to the development of metadata application profiles"...